Penilaian Risiko Keselamatan Dan Kesehatan Kerja Pada Pekerjaan Kolom, Balok dan Pelat Lantai (Studi Kasus Proyek Konstruksi Pembangunan Gedung Kantor Kejaksaan Tinggi Provinsi Riau) - Ermiyati Ermiyati; Fakhri Fakhri; Citra Hockiana (Universitas Medan Area, 2021)
The implementation of construction activities, especially building construction work, has a high risk of accidents because each stage of the work contains many potential hazards that can be detrimental. This study aims to determine the highest occupational accident risk and its control in column, beam and floor slab work. The research method was carried out through field observations as well as interviews and surveys from several sources. The results of this study are jobs that contain the highest risk value, namely in the steps of installing work and dismantling column formwork, installing scaffolding, and installing wooden beams on beam and floor slab work where each step of this work has a risk level value of 6, this has high level of risk . For hazard control, the contractor carries out several work programs with the aim of reducing the potential for work accidents. As for the program in the form of Toolbox, Safety Patrol, Safety Weekly Meeting, Safety Talk, Fooging and Extrapuding.